2013
DOI: 10.1186/1471-2164-14-800
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of microevolution of Salmonella Typhimurium during a series of egg-associated outbreaks linked to a single chicken farm

Abstract: BackgroundThe bacterium Salmonella enterica serovar Typhimurium (S. Typhimurium) is one of the most frequent causes of foodborne outbreaks of gastroenteritis. Between 2005–2008 a series of S. Typhimurium outbreaks occurred in Tasmania, Australia, that were all traced to eggs originating from a single chicken farm. We sequenced the genomes of 12 isolates linked to these outbreaks, in order to investigate the microevolution of a pathogenic S. Typhimurium clone in a natural, spatiotemporally restricted population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 59 publications
7
59
0
2
Order By: Relevance
“…The S. Typhimurium core genome contained 956 (33.45%) more genes than the Salmonella core genome, which contains only 2,882 genes as defined previously (16). We showed that the use of the STCG or the STCG plus core IGRs increases the resolution of the genome sequencing for epidemiological typing using published and epidemiologically investigated outbreaks (14,15,25,26).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The S. Typhimurium core genome contained 956 (33.45%) more genes than the Salmonella core genome, which contains only 2,882 genes as defined previously (16). We showed that the use of the STCG or the STCG plus core IGRs increases the resolution of the genome sequencing for epidemiological typing using published and epidemiologically investigated outbreaks (14,15,25,26).…”
Section: Discussionmentioning
confidence: 90%
“…To evaluate the performance of the S. Typhimurium core genome (STCG with and without core IGRs) typing, 21 strains from SARA sequenced in this study and 94 isolates from 13 different outbreaks were used (see Table S2 in the supplemental material) (14,15,25,26). The selection of outbreaks was either based on representative phage type or ST, including DT135, DT135a, U292, DT3, DT104, DT12, DT120, and ST313.…”
Section: Methodsmentioning
confidence: 99%
“…There are three different mutation rates reported for S. Typhimurium. The lowest rate is 1.9 ϫ 10 Ϫ7 substitution per site per year, estimated for ST313, causing invasive infections in Africa (26); the intermediate rate is 3.4 ϫ 10 Ϫ7 substitution per site per year, obtained from the epidemic DT104 infections (27); and the highest rate is 1.2 ϫ10 Ϫ6 substitution per site per year, obtained from a DT135a outbreak (28). Our estimate of the mutation rate is the highest but is only 12% higher than the previous highest estimate.…”
Section: Resultsmentioning
confidence: 99%
“…Bununla birlikte gıda kaynaklı Salmonella infeksiyonlarının irdelendiği birçok çalışmada S. enterica subsp. enterica serovar Typhimurium en sık etken olarak tespit edilmiş ve en çok tavuk eti ve çiğ yumurta tüketimiyle ilişkili bulunmuştur (6,16). Çalışmamızda her ne kadar gıda örneklerinde herhangi bir üreme tespit edilmemiş olsa da, tüm olguların aynı yemek şirketi tarafından hazırlanmış menüyü aynı öğünde yemiş olması, tavuk eti yiyenlerde yakınmaların gelişmesi, sadece pilav ve ayran tüketenlerde herhangi bir yakınmanın olmaması, salgının kaynağının tavuk eti olduğunu düşündürmüş-tür.…”
Section: İrdelemeunclassified
“…enterica serovar Typhimurium (S. typhimurium) ve S. enterica subsp. enterica serovar Enteritidis (S. enteritidis), gıda kaynaklı salgın dahil gastroenteritlerin en sık etkenidir (6). Salmonella infeksiyonlarına en çok neden olan gıdaların başında ise kontamine tavuk eti ve yumurta gelmektedir (7,8).…”
Section: Introductionunclassified